Gravitational lensing and microlensing - Mollerach, Silvia (World Scientific, 2002)
Includes bibliographical references (p. 175-187) and index.; This book provides a comprehensive and self-contained exposition of gravitational lensing phenomena. It presents the up-to-date status of gravitational lensing and microlensing, covering the cosmological applications of the observed lensing by galaxies, clusters and the large scale structures, as well as the microlensing searches in the Local Group and its applications to unveil the nature of the galactic dark matter, the search for planetary objects and the distribution of faint stars in our galaxy. Gravitational Lensing and Microlensing is pitched at the level of the graduate student interested in the issues of astrophysics and cosmology, and should be useful for specialist researchers as well.